2019
DOI: 10.1002/hep4.1332
|View full text |Cite
|
Sign up to set email alerts
|

Correlation of Immune Markers With Outcomes in Biliary Atresia Following Intravenous Immunoglobulin Therapy

Abstract: Biliary atresia is a progressive fibroinflammatory cholangiopathy of infancy that is associated with activation of innate and adaptive immune responses targeting bile ducts. A recently completed multicenter phase I/IIA trial of intravenous immunoglobulin in biliary atresia did not improve serum total bilirubin levels at 90 days after hepatoportoenterostomy or survival with the native liver at 1 year. A mechanistic aim of this trial was to determine if the peripheral blood immunophenotype was associated with cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 50 publications
0
9
0
Order By: Relevance
“…Many of the KEGG pathways were related to the immune response, which was consistent with some previous studies. [22,23] A recent study has demonstrated that IL-17A signaling pathway was probably involved in chronic inflammation of the bile duct in primary biliary cirrhosis, [24] in which, chronic inflammation was associated with biliary innate immune responses. [25] It seems to be linked to our study.…”
Section: Discussionmentioning
confidence: 99%
“…Many of the KEGG pathways were related to the immune response, which was consistent with some previous studies. [22,23] A recent study has demonstrated that IL-17A signaling pathway was probably involved in chronic inflammation of the bile duct in primary biliary cirrhosis, [24] in which, chronic inflammation was associated with biliary innate immune responses. [25] It seems to be linked to our study.…”
Section: Discussionmentioning
confidence: 99%
“…GVHD-like immune interaction (CD8+ effector lymphocytes are MC cells), whereas an indirect cause implies that MC cells are cytokeratin-positive cells, which are targets of autologous T lymphocytes. The other possible indirect cause is regulatory T cell (Treg) dysfunction (6)(7)(8), which is affected by MMc, leading to host immune responses toward self-antigens. To distinguish these alloimmune reactions, we quantified MC-DNA separately in the buffy coat, which reflects the number of maternal lymphocytes and in the plasma, representing the number of MC cells incorporated in host tissue that shed their DNA.…”
Section: Discussionmentioning
confidence: 99%
“…DB and ALB are factors reflecting the excretory and synthetic functions of liver; the results indicate that only patients with excellent comprehensive liver functions can survive with their native liver. Some studies have been reported about predicting NLS for infants after KPE, most focused on factors before jaundice resolution, and some are not routine parameters, [9][10][11][12][13][14][15] the predictive values are not certain.…”
Section: Kpe Remains the First Surgical Choice For Biliary Atresia Co...mentioning
confidence: 99%